4 Nurse-led interventions for people with multimorbidity: what are they and how do they improve outcomes? A mixed-methods systematic review. (14th March 2023) - McParland, Chris; Johnston, Bridget; Cooper, Mark
Abstract : Background: People with 2 or more chronic conditions (multimorbidity) are at risk of receiving fragmented and inefficient care. In order to develop a nurse-led intervention for people with multimorbidity and palliative conditions, we sought to explore the types of existing nurse-led multimorbidity interventions and what outcomes were positively affected by them. Methods: Mixed-methods systematic review following Joanna Briggs Institute (JBI) methodology. Cochrane CENTRAL, CINAHL, Embase and MEDLINE were searched from inception in October 2020 alongside grey literature. Quality appraisal was conducted using JBI tools; low-quality studies were not excluded but did not generate any novel findings in sensitivity analyses. Interventions were classified using adapted Cochrane EPOC taxonomy and outcomes were mapped to the Core Outcome Set for Multimorbidity Research. PROSPERO ID: CRD42020197956. Results: 20 eligible studies were included. Case-management or transitional care interventions were most common, and often featured nurses in advanced practice, supported self-management, individualised care-planning and care coordination. Predictive modelling to identify people at high-risk of healthcare utilisation was also common. Positive effects were most consistently reported in relation to person-centred outcomes (such as patient-perceived quality of care, quality of life, quality of communication with healthcare providers), with mixed effects observed on healthcare utilisation, mortality and other core outcomes. Conclusions: Nurse-led multimorbidity interventions are agreeable to patients but their effects on service use and costs are mixed. Complexity in populations and intervention types mean that localised development and iterative evaluation of interventions may be the most effective approach to improving outcomes in this population. We propose a broad, theoretically-grounded model of nurse-led interventions for people with multimorbidity, which we intend to use as a basis for our intervention to improve outcomes in people with multimorbidity and palliative conditions.